COUNSELING GUIDANCE FOR CHILDREN CONVICTED OF VIOLENCE THROUGH COACHING AT THE JAKARTA CLASS II SPECIAL TRAINING INSTITUTION FOR CHILDREN - Arysa, Sabrina Alfi; Priyatmono, Budi (Universitas Nusa Cendana, 2025)
This study discusses the implementation of counseling guidance for juvenile inmates involved in violent cases at the Special Child Development Institution (LPKA) Class II Jakarta. Counseling guidance at LPKA plays an important role in the psychological recovery of juvenile inmates, intending to help them understand themselves and their environment, as well as develop their potential optimally. This research uses a qualitative approach with interviews and observations as data collection methods. The results indicate that counseling guidance is effective in improving the behavior of juvenile inmates and increasing their readiness to reintegrate into society. Barriers to the implementation of counseling were also identified, including limited resources and consistency in the development programs. Keywords: Counseling Guidance; Juvenile Inmates; Rehabilitation